KLASIFIKASI EMOSI TOKOH GUNARTO DALAM NASKAH DRAMA AYAHKU PULANG KARYA USMAR ISMAIL (ANALISIS PSIKOLOGI SASTRA) - Yogi Rizky Pratama (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study is to describe the classification of emotions in the script of the Ayahku Pulang by Usmar Ismail. This research is a type of qualitative descriptive research that is described in the findings in the form of quotations contained in the manuscript Ayahku Pulang by Usmar Ismail. The data in this study uses data in the form of quotations containing forms of fear, anger, and love. In this type of qualitative descriptive research, the author uses as a step to describe the classification of emotions in this manuscript.The results of this study are in the form of a description of fear, anger, and love for the character Gunarto in the script of the drama Ayahku Pulang by Usmar Ismail. As for the form of fear, data such as “Jadi, jadi Ayah meloncat ke dalam sungai?”. As for the form of anger “Maimun! Kapan kau mempunyai seorang Ayah!”. As for the form of love “Aku sudah merasa bahagia kalau kau bahagia, Narto. Karena nasibku bersuami tidak baik benar. Dan kata orang bahagia itu akan turun kepada anaknya. Malam hari raya sewaktu ia pergi itu, tak tahu aku apa yang mesti aku kerjakan? Tetapi…” the three aspects of the classification of the emotions of this character are clearly depicted in the script of this play.